2011
DOI: 10.1007/s10404-010-0760-7
|View full text |Cite
|
Sign up to set email alerts
|

A modified microfluidic chip for fabrication of paclitaxel-loaded poly(l-lactic acid) microspheres

Abstract: In this article, we present a simple PDMS surface modification method based on poly(vinyl alcohol)/glycerol (PVA/Gly) solution immersion, self-assembled absorption, and heat treatment. The results of contact angle and ATR-FTIR demonstrate the superhydrophilic surface in modified PDMS. It can allow for the stable production of monodisperse droplet in a highly reproducible manner. In addition, we demonstrate the fabrication of monodisperse paclitaxel (PTX) loaded poly(L-lactic acid) (PLLA) microspheres on this k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…We evaluated the level of the surface hydrophilicity induced by two commercially available PVA solutions commonly used in PDMS surface modification [27][28][29][32][33][34] . We applied PVA solutions with 87-90% and 99+% hydrolysis degrees on PDMS surfaces that were plasma oxidized under the same conditions (50 W for 1 min) and concluded that the former had a more profound effect on the PDMS surface chemistry both in the short and the long term (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the level of the surface hydrophilicity induced by two commercially available PVA solutions commonly used in PDMS surface modification [27][28][29][32][33][34] . We applied PVA solutions with 87-90% and 99+% hydrolysis degrees on PDMS surfaces that were plasma oxidized under the same conditions (50 W for 1 min) and concluded that the former had a more profound effect on the PDMS surface chemistry both in the short and the long term (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental data show that the PVA-treated PDMS surfaces retain their hydrophilicity in the long term. We leveraged PVA solutions with two distinct hydrolysis degrees (87-90% and 99+%) because these are widely used for surface modification in PDMSbased microfluidics 33,34 . Based on a wettability study, we found that PVA with a hydrolysis degree of 87-90% was more efficient in both the short and long term compared with PVA with a 99+% hydrolysis degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the use of solution reactions to generate complex shapes of nano and micro structures almost seems serendipitous, microfluidics technology offers a unique route toward synthesizing such complex, monodisperse particles with predetermined size and shape with relative ease (Takasi and Takeshi 2010;Helgeson et al 2011;He et al 2011). Thus, microfluidics technology is receiving increasing attention for synthesizing customized particles with spherical or non-spherical morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a slot-structure, only the tail of guided waves (evanescent wave) could interact with analyte, and this configuration would significantly reduce the sensitivity of the device. To avoid absorption of lightwave by PDMS, which is a mid-IR absorptive between λ = 2.6 μm to λ = 4 μm, 38 we introduced an additional SiO 2 layer that conformally covers the Si−SiO 2 −Si waveguide to prevent direct contact between the SiO 2 slot-waveguide and the PDMS chamber. Figure 3 shows micrographs of the fabricated nanofluidic channels and mid-IR slot-waveguides obtained by scanning electron microscope (SEM).…”
mentioning
confidence: 99%